2003
DOI: 10.1021/jp0303568
|View full text |Cite
|
Sign up to set email alerts
|

Photoanodic Properties of Sol−Gel-Derived Fe2O3 Thin Films Containing Dispersed Gold and Silver Particles

Abstract: α-Fe2O3 films containing dispersed Au and Ag particles 5−20 nm in size were prepared on nesa silica glass substrates by the sol−gel method, using solutions of a mole ratio Fe(NO3)3·9H2O: (HAuCl4·4H2O or AgNO3):CH3COCH2COCH3:CH3OCH2CH2OH = 1:0.06:2:20 as the coating solution. The anodic photocurrent−potential characteristics and the action spectra were investigated in a three-electrode cell employing the film electrode as the working electrode. When the film electrode was illuminated with intense white light, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 47 publications
3
79
0
Order By: Relevance
“…The XRD results showed that both anatase and rutile were present in the Au-TiO 2 /ITO films. In addition, the crystalline Au can only be found in the Au-TiO 2 /ITO films with a Au content higher than 1.5% as a broad peak at around 2 = 44 °, according to Watanabe et al [36]. [18,37,38].…”
Section: Characteristics Of Tio 2 /Ito and Au-tio 2 /Ito Filmsmentioning
confidence: 98%
“…The XRD results showed that both anatase and rutile were present in the Au-TiO 2 /ITO films. In addition, the crystalline Au can only be found in the Au-TiO 2 /ITO films with a Au content higher than 1.5% as a broad peak at around 2 = 44 °, according to Watanabe et al [36]. [18,37,38].…”
Section: Characteristics Of Tio 2 /Ito and Au-tio 2 /Ito Filmsmentioning
confidence: 98%
“…[2][3][4][5][6][7][8][9] In addition, it is possible for many of these oxides to intercalate-deintercalate Li ions into the layered (2D) or network (3D) structure. [1,3] In recent years, nanoparticles, nanotubes, and thin films of a-Fe 2 O 3 (hexagonal corundum structure) have been studied for their magnetic properties, [10] photoelectrochemical splitting of water to hydrogen, [11] photoanodic properties, [12] field-emission behavior, [13] use as potential gas sensors [14] and as electrodes for LIB applications. [14][15][16][17][18][19] Larcher et al [16] have shown that 0.5 moles of Li can be reversibly intercalated into nanoparticles (20 nm) of a-Fe 2 O 3 in the potential range 1.5-4.0 V (vs. Li).…”
Section: Introductionmentioning
confidence: 99%
“…1 Introduction Efforts in the field of development of new technologies for manufacturing of nanostructured photoelectrodes and investigations of peculiar properties of their photoelectrochemical behaviour became especially more active in last years (see, in particular, [1][2][3][4]). Thin film photoelectrodes with nanoporous structure are desirable for photoelectrochemical splitting of water due to their large surface area and high catalytic activity.…”
mentioning
confidence: 99%